A study on consumer attitudes toward life insurance products concerning Life Insurance Corporation of India, Kakinada - P, HARI KUMAR; PVV, Satya Narayana; P. VIJAYA KUMAR (International Journal of Psychosocial Rehabilitation, 2019)
In the context of consumer behaviour, acquisition, use, and disposal may occur in a dynamic sequence throughout time. Individuals’ choices to spend their available resources (money, time, effort) on consumption-related things are the focus of the study of consumer behaviour. Customers of LIC of India in Kakinada were asked to fill out a survey on their attitudes, values, beliefs, and behaviours. This research examined the micro-variables and drivers of policyholder behaviour in great detail. The study’s primary goal was to determine what factors influence policyholders’ decisions on purchasing insurance. The study’s primary goal is to understand better the different external and internal effects on policyholder decision making.’ For this research, the Life Insurance Corporation of India, a well-known corporation in India and worldwide, serves as the universe. The researcher decided to study Kakinada’s branches in light of the aims above. After conducting pilot research, the Questionnaire/schedule was administered. The pilot study’s participants have been included in the actual sample size for statistical analysis. Schedules/Questionnaires were printed in quantities of 450 and handed to survey participants, who completed them in person at various branches of the chosen organization at the various locations previously indicated. The researcher determined that just a tiny fraction of all attempted interviews were completed. This study had a 96.6 per cent response rate. Four hundred fifty blank questionnaires were sent to the participants, and 400 completed questionnaires were returned to the researcher.